A survey on factors for late antenatal booking amongst pregnant women attending a Community Health Care Centre in Tembisa, Gauteng Province, South Africa - Ibeziako, Ozoemena Joan (University of Pretoria, 2025)
Dissertation (MMed (Family Medicine))--University of Pretoria, 2023.